Willingness to Pay for Mortality Risk Reductions: Does Latency Matter? - Anna Alberini; Maureen Cropper; Alan Krupnick; Nathalie B. Simon (Fondazione Eni Enrico Mattei (FEEM), 2004)
Using results from two contingent valuation surveys conducted in Canada and the U.S., we explore the effect of a latency period on willingness to pay (WTP) for reduced mortality risk using both structural and reduced form approaches. We find that delaying the time at which the risk reduction occurs by 10 to 30 years reduces WTP by more than half for respondents in both samples aged 40 to 60 years. Additionally, we estimate implicit discount rates equal to 8% for Canada and 4.5% for the U.S. both well within the range established previously in the literature.
Keywords: Q51; Q58; 330; Value of a statistical life; Mortality risks; Benefit-cost analyris; Gesundheit; Zahlungsbereitschaftsanalyse; Sterblichkeit; Vergleich; USA; Kanada